Gambaran Konsumsi Protein Hewani, Konsumsi Tablet Tambah Darah dan Kejadian Anemia Siswi SMAN 1 Payangan Kabupaten Gianyar - Ni Kadek Windaningsih; I Ketut Kencana; I Made Suarjana (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2018)
The prevalence of anemia in Indonesia in female students is still quite high at 21.7%. Female students are one of the groups that are susceptible to anemia because they have menstruation every month so much loss of iron. One cause of iron nutritional anemia is the lack of consumption of animal protein. This study aims to determine the description of animal protein consumption, consumption of fe suplementation and anemia incidence for female students in SMA N 1 Payangan Gianyar regency. The type of the research was used observational with the cross-sectional design. The sample of the students of class XI was amounted to 86 samples. The results showed that more half the level of animal protein consumption of the sample is good amounted to 35 samples (41%). Consumption data of fe suplementation that did not drink amounted to 11 samples (12.8%). The results for examination of hemoglobin content, the samples classified into anemic has amounted to 27 samples (31%). The data analysis showed that consumption of animal protein had a positive relationship to the incidence of anemia. The higher the consumption of animal protein the smaller the incidence of anemia. Female students should consume animal protein in accordance with the need to form sufficient hemoglobin levels.Kata Kunci: Consuming of animal protein, Anemia, Consuming of fe suplemetation, High school female student